An introduction to black holes, information, and the string theory revolution : the holographic universe - Susskind, Leonard; Lindesay, James (World Scientific, 2005)
Over the last decade the physics of black holes has been revolutionized by developments that grew out of Jacob Bekenstein's realization that black holes have entropy. Steven Hawking raised profound issues concerning the loss of information in black hole evaporation and the consistency of quantum mechanics in a world with gravity.